FORENSIC ASPECTS OF HOMICIDE-SUICIDE PHENOMENA - Gojkovic, Tijana; Opankovic, Ana; Atanasijevic, Tatjana; Petrovic, Tijana (HEALTH CARE, 2023)
Introduction/Aim: Homicide-suicides (H-S) are those suicides that occur after a person commits one or more murders. This social phenomenon occurs in context of the family tragedies. The frequency is low, but due to the tragic outcome, there is a need for researchers worldwide to address this topic. The aim of this study was to analyze the forensic aspects of H-S with special reference to the demographic characteristics of the perpetrator, the way of committing murder and suicide, and the mutual relationship between the victim and the perpetrator of H-S, in order to understand the circumstances under which it occurs, as well as the risk of this social phenomena. Methods: This retrospective descriptive study covered eight-year (2015-2022) period. The study included individuals who committed suicide after committing one or more homicides. Data were obtained from autopsy and police reports from Institute of Forensic Medicine in Belgrade. Demographic characteristics, circumstances of the case, number and localization of wounds, hetero-amnestic data, relationships between victims and killers, motives and toxicological analysis were analyzed. Results: 19 cases of H-S and 39 victims were observed. The majority of victims were female (80%), and the killers were male (89.5%). Killers were five years older than victims. The highest percentage of murderers were not highly educated (84.2%), and lot of them had a psychiatric diagnosis (47.4%). For both components, firearms were most often used (70-73.7%). Most of them were in family (90%), specifically in emotional relationship (60%). The leading motives were jealousy (45%), family and financial problems (25%) and mercy (15%). Conclusion: H-S occurs within the family, most often using firearms by men from the lower social class, who have previously shown critical behavior. The reasons that lead to H-S are jealousy, quarrels and illness. By identifying some of the components of H-S, it is possible to prevent their occurrence